2011
DOI: 10.1029/2011gl047968
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-hemispheric coupling effects on the polar summer mesosphere

Abstract: The state of the mesosphere is connected to the lower atmosphere through various dynamical coupling processes. Nine years of Odin satellite observations of noctilucent clouds (NLC) have been analyzed as tracers for such processes. Inter‐hemispheric coupling from the winter stratosphere and troposphere is confirmed to have a major influence on the summer mesosphere. Intra‐hemispheric coupling from the spring/summer stratosphere, on the other hand, can control the onset of the NLC season. Most prominently, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…The transition of stratospheric winds in the NH takes place much earlier than in the SH, and PMSE in the NH appear several weeks after this transition. For the NH it is obvious that stratospheric wind transition is not the most important ingredient causing low temperatures and PMSE/NLC/PMC in the NH mesosphere (see, for example, Latteck et al, 2008;Gumbel and Karlsson, 2011;Benze et al, 2012, and references therein).…”
Section: Comparison Of Pmse With Stratospheric Wind Fieldmentioning
confidence: 99%
“…The transition of stratospheric winds in the NH takes place much earlier than in the SH, and PMSE in the NH appear several weeks after this transition. For the NH it is obvious that stratospheric wind transition is not the most important ingredient causing low temperatures and PMSE/NLC/PMC in the NH mesosphere (see, for example, Latteck et al, 2008;Gumbel and Karlsson, 2011;Benze et al, 2012, and references therein).…”
Section: Comparison Of Pmse With Stratospheric Wind Fieldmentioning
confidence: 99%
“…NLC mainly exist in the polar regions, while they get rare around 55° latitude. Extended data sets of NLC occurrence exist by visual observations from the ground [e.g., Fogle and Haurwitz , ; Gadsden , ; Romejko et al ., ; Kirkwood et al ., ] and are complemented in recent years by instrumented observations from the ground as well as from space [e.g., DeLand et al ., ; Fiedler et al ., ; Gumbel and Karlsson , ]. The Aeronomy of Ice in the Mesosphere (AIM) satellite has been launched with several instruments as a dedicated mission to examine NLC/PMC in both hemispheres [e.g., Russell et al ., ; Chandran et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Kirkwood et al (2008) reported a higher position for the mesopause during Novemeber 2007; they attributed this anomaly to the filtering of gravity waves by winds in the middle atmosphere. Gumbel and Karlsson (2011) found that the onset of the season for polar mesospheric clouds in the SH summer of 2010-2011 was delayed by several weeks. This coincided with a delayed breakdown of the westerly jet in the stratosphere during this summer season.…”
Section: Summer Mltmentioning
confidence: 99%